2013
DOI: 10.1038/npp.2013.105
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Functional Effects of Sazetidine-A and Varenicline During Nicotine Withdrawal

Abstract: Smoking is the largest preventable cause of death in the United States. Furthermore, a recent study found that o10% of quit attempts resulted in continuous abstinence for 1 year. With the introduction of pharmacotherapies like Chantix (varenicline), a selective a4b2 nicotinic partial agonist, successful quit attempts have significantly increased. Therefore, novel subtype-specific nicotinic drugs, such as sazetidine-A, present a rich area for investigation of therapeutic potential in smoking cessation. The pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 99 publications
3
35
0
Order By: Relevance
“…For example, in naive animals, shortterm and long-term varenicline administration is anxiolytic in the NIH test (Turner et al, 2010). However, in nicotineexperienced animals, short-term administration of varenicline during nicotine withdrawal fails to alleviate anxiety-like behavior (Turner et al, 2013b), suggesting a differential effect of varenicline based on the drug experienced state of the subject. Additionally, a recent study in smokers identified anxiety as one of the symptom domains in which varenicline treatment was ineffective (Cinciripini et al, 2013).…”
Section: Anxiolytic Effects and Nachr Regulation Of Abt-089 Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, in naive animals, shortterm and long-term varenicline administration is anxiolytic in the NIH test (Turner et al, 2010). However, in nicotineexperienced animals, short-term administration of varenicline during nicotine withdrawal fails to alleviate anxiety-like behavior (Turner et al, 2013b), suggesting a differential effect of varenicline based on the drug experienced state of the subject. Additionally, a recent study in smokers identified anxiety as one of the symptom domains in which varenicline treatment was ineffective (Cinciripini et al, 2013).…”
Section: Anxiolytic Effects and Nachr Regulation Of Abt-089 Discussionmentioning
confidence: 99%
“…The NIH paradigm is a sensitive measure for potential anxiolytic drugs and anxiogenic effects of withdrawal on both acute and extended drug administration paradigms (Dulawa et al, 2004;Dulawa and Hen, 2005). The NIH test is sensitive to the anxiolytic effect of long-term nicotine (Turner et al, 2010(Turner et al, , 2013b and the anxiogenic effect of 24-hour withdrawal from nicotine (as shown in Fig. 1).…”
Section: Anxiolytic Effects and Nachr Regulation Of Abt-089 Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pumps were filled with 100μL of either sterile saline or nicotine hydrogen tartrate (Sigma Co, St. Louis, MO) dissolved in saline, and implanted subcutaneously in isoflurane-anesthetized mice under aseptic surgical conditions. Nicotine was administered at a dose of 18mg/kg/day (reported as free base) previously reported to desensitize nAChRs (Turner et al 2010; Turner et al 2013; Wilkinson et al, 2013) and produce reversal learning deficits in mice (Ortega et al 2013). …”
Section: Methodsmentioning
confidence: 99%